Soluble immune checkpoint molecules: mechanism of formation, function, role in malignant neoplasms - T. V. Glazanova; I. E. Pavlova; E. V. Kuzmich; L. N. Bubnova (Медицинская иммунология, 2025)
Immune checkpoints (ICs) represent a broad set of stimulatory and inhibitory signaling pathways playing an important role in regulation of immune responses. Initially, ICs have been considered solely as cell membrane-bound receptor and ligand systems, triggering or blocking immune cell function. Over the past decade they have been proven to exist in soluble forms (sICs). sICs are biologically active regulators involved in paracrine and systemic modulation of immune responses, similar to cytokines. Normally, sICs exert both stimulatory and inhibitory effects on the immune system, and their balance may be disturbed in many malignant neoplasms, COVID-19, HIV infection. There is a lot of data on the connection between sICs and various diseases, but a number of key aspects of their biology have not been fully clarified. The most widely studied are PD-1 (programmed death receptor-1) and its ligands PD-L1 and PD-L2, CTLA-4 (cytotoxic T lymphocyte antigen-4), TIM-3 (T cell immunoglobulin and mucin-domain containing-3), VISTA (V-domain Ig-containing suppressor of T cell activation). The mechanisms of soluble form formation are complex and diverse and include alternative splicing, cleavage of membrane ectodomains, and proteolytic cleavage. The most important molecular mechanisms underlying the synthesis and release of sPD-1 and sPD-L1 are alternative splicing of mRNA and translation of isoforms lacking transmembrane domains, while the formation of sTIM-3 occurs by cleaving the extracellular regions of transmembrane proteins by protease ADAM10. The review article provides data on the main sICs, including sPD-1, sPD-L1, exosomal sPD-L1, sCTLA-4, and several others. The molecular mechanisms of their formation, biological functions in maintaining immune homeostasis, prognostic significance of changes in their content are described in patients with solid malignant tumors (nonsmall cell lung cancer, hepatocellular cancer, breast cancer, kidney cancer, skin cancer, gastric cancer, etc.), as well as for hematologic malignancies (lymphoma, chronic lymphocytic leukemia, acute myeloblastic leukemia, multiple myeloma).